Loeffler’s endocarditis with hypereosinophilic syndrome – a rare case study report (Indian Journal of Case Reports, 2025)
This case report describes the clinical presentation of Loeffler’s syndrome in a 50-year-old male non-diabetic and non-hypertensive who presented with complaints of pedal edema and breathlessness, signifying New York Heart Association III cardiac failure. There was mild itching, which was intermittent and insidious in onset. On general examination, there were pallor and bilateral pedal edema, which were pitting in nature. Differential leukocyte count showed 34.0% polymorphs and eosinophilia with an eosinophil count of 51%. Electrocardiography depicted low-voltage complexes. Chest X-ray showed cardiomegaly with increased computed tomography (CT) ratio >0.6 and blunting of costophrenic angles. 2D echocardiography showed apical obliteration and biatrial enlargement with increased left atrial (LA) volume. A restrictive filling pattern was observed on color Doppler, indicating grade III diastolic dysfunction with an E/A of 4.5 and E/E’ of 14. Contrast-enhanced CT was suggestive of the presence of left ventricular thrombus. The diagnosis was Loeffler’s endocarditis with hypereosinophilic syndrome with congestive cardiac failure.